Assessing the efficiency of application of project management in the field of engineering of innovative developments - Myronenko, Oleksii (Eastern-European Journal of Enterprise Technologies, 2023)
This paper investigates the peculiarities and effectiveness of using project management in the field of engineering of innovative developments. The relevance of the topic relates to the fact that the process of innovative development is characterized by its duration and the uncertainty of the probability of obtaining specific results. Such a feature determines the need to build such a project management system for the engineering of innovative developments, which would ensure the definition of sub-stages of this process, the assessment of the degree of their implementation, and the determination of the results of these stages. The object of this study is the project management system of the engineering projects of innovative developments of the company Hokord Ltd. The research used methods of statistical analysis with the distribution of data into control and test groups. This distribution made it possible to reveal the impact of the implementation of project management on the effectiveness of project management. The study solves the problem of determining the effectiveness of project management in comparison with traditional approaches to project management. The results of the study show that the implementation of project management in the field of engineering of innovative developments has led to the improvement of project management and an increase in their efficiency. Implementation of project management made it possible to establish new project statuses and reduce the share of canceled or closed projects, while the share of successfully completed projects increased. Unlike other studies, quantitative indicators of the effectiveness of project management were established - the duration of project implementation was reduced by an average of 11 %. The implementation of project management also improved the assessment and allocation of project priorities, a decrease in the share of projects with high priority, and an increase in the share of projects with low and uncertain priority was revealed